The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4187/respcare.05660
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Noninvasive Ventilation Protocol in Hospitalized Children With Acute Respiratory Failure

Abstract: We observed that the implementation of an NIV management protocol that integrates initiation and discontinuation criteria for NIV is feasible. However, its use showed no advantages over a non-protocolized strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…The severity of acute respiratory failure in previous CNEP analyses (MWS score ≥ 5 10 ) was greater than that of the present patients. A previous study suggested that early intervention before the possible state of endotracheal intubation could avoid disease progression to severe clinical symptoms 16 . Our children with acute upper or lower respiratory disease had MWS scores of 3–4, which indicated mild respiratory symptoms without the requirement for immediate intubation therapy.…”
Section: Discussionmentioning
confidence: 52%
“…The severity of acute respiratory failure in previous CNEP analyses (MWS score ≥ 5 10 ) was greater than that of the present patients. A previous study suggested that early intervention before the possible state of endotracheal intubation could avoid disease progression to severe clinical symptoms 16 . Our children with acute upper or lower respiratory disease had MWS scores of 3–4, which indicated mild respiratory symptoms without the requirement for immediate intubation therapy.…”
Section: Discussionmentioning
confidence: 52%
“…Die nichtinvasive Beatmung zu Behandlung der ARI hat ihren festen Stellenwert in der Behandlung von Säuglingen und Kinder auf der pädiatrischen Intensivstation. Die Evidenz zum Nutzen der NIV kommt u. a. aus kleineren randomisierten Studien 499 500 501 502 503 504 505 506 507 508 , Cross-over-Studien 509 510 511 512 , prospektiven 90 94 101 513 514 515 516 517 518 519 520 521 522 523 524 525 526 527 528 529 530 531 532 533 534 535 536 537 538 539 und retrospektiven Kohortenstudien 91 93 95 97 540 541 542 543 544 545 546 547 548 549 550 551 552 553 554 555 556 557 558 559 560 561 562 563 . Trotz der vielen Studien ist aufgrund der meist kleinen Fallzahlen und Heterogenität der untersuchten Kohorten eine Überlegenheit von NIV im Vergleich zu Standardtherapie für viele Indikationen im Kindesalter außerhalb der Neugeborenen Periode unzureichend belegt.…”
Section: Ari Bei Kindern Und Jugendlichenunclassified